A multimodal analysis on a vocational English book and its effect on students’ English proficiency - Sidabutar, Usman; Sinaga, Nenni Triana; Sitorus, Nurhayati; Lestari, Febrika Dwi (Linguistics and Culture Review, 2021)
The digitization of education is the use of technology as an aspect of the learning system, from the curriculum to the education system, which has a very big influence on innovation. As society and academic demand increase in the modern era, the online learning system (OLS) is encountered by society and academics. The multimodal approach refers to the huge learning competence in English ability as if the method or application is integrated in a digitizing manner. The multimodal approach contains using images, verbal and visual integration with words or text which provides meanings in the mode of communication. The process of analyzing and disclosing the text will give essence to the meaning of a picture message in a printed book will reveal projection, enhancement, concurrence. All of which are discussed based on linguistic analysis to relate the text to the general characteristics of language both verbally and visually. Systemic function Linguistics based on the concept of metafunction has ideational, interpersonal, and textual components linking the internal forms of language and their use in semiotic social contexts will be enacted to the research. The research will use descriptive and qualitative methods.